The role of legislative change in reducing domestic violence against women in India - Aparna Mathur; Sita Nataraj Slavov (American Enterprise Institute (AEI), 2016)
This paper investigates whether two legislative changes aimed at empowering women did in fact lower the risk of domestic violence for women in India. We use the National Family Health Survey, a nationally representative household dataset to explore this issue. The first legislative change we exploit is a natural experiment wherein five states made amendments to their inheritance laws allowing daughters equal status as sons in the right to inherit the joint property of the father. We find no statistically significant effect of this arguably exogenous improvement in women's autonomy on their likelihood of being victims of domestic abuse. The second change was geared at improving political representation of women by reserving at least one-third of seats in the local Panchayats for women. The change to representation was implemented at different dates depending on the timing of elections. Our results suggest that improved representation increased the probability of violence. There are two competing explanations for these results. First, women may have experienced retaliation by men who feared the erosion of their power and opposed the policy change. Second, the policy change may have made women more willing to report violence to interviewers. Given our finding that improved representation may have also increased the rate of employment for women (a general measure of empowerment), we speculate that our results may be driven by an increase in the willingness of women to discuss violence with interviewers.
Keywords: A; 330; India; domestic violence